Upaya Meningkatkan Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti melalui Cooperative Learning Tipe Jigsaw Pada Siswa Kelas V SDN 02 Sitiung: Efforts to Improve Learning Outcomes of Islamic Religious Education and Ethics through Jigsaw Type Cooperative Learning in Grade V Students of SDN 02 Sitiung - eka juliarti (Perkumpulan Doktor Indonesia Maju (PDIM), 2022)
This research starts from the fact in the field that learning carried out by teachers often use conventional learning models, where teachers are always the center of learning (teaching centered) so that the learning outcomes of PAI and BP students are not as expected. This research aims to improve the learning process of PAI and BP in the classroom so that it can improve the learning outcomes of PKn in class V SD 02 Sitiung. The approach used in this study is a qualitative approach. Data collection was carried out with observations, interviews, tests, and observation sheets. Jigsaw type cooperative learning model is a learning model that places students in study groups of 4 or 5 students. This learning model is done through stages, starting from conveying learning objectives, providing information about the material studied, organizing students into groups, reading/ giving materials, placing students in expert groups, presenting materials to members of the original group, holding quizzes/ tests , give an award. From the results of the study, it is seen that by using the Jigsaw type cooperative learning model can improve the learning outcomes of PAI and BP students in class V SDN 02 Sitiung. From the results of student learning for the assessment of results in cycle I obtained a value with an average of 72 and there was an increase in student learning outcomes in cycle II that is the assessment of results obtained a value with an average of 87.